Anticonvulsant activity, teratogenicity and pharmacokinetics of novel valproyltaurinamide derivatives in mice - Isoherranen, Nina (2003)
1. The purpose of this study was to synthesize novel valproyltaurine (VTA) derivatives including valproyltaurinamide (VTD), N-methyl-valproyltaurinamide (M-VTD), N,N-dimethyl-valproyltaurinamide (DM-VTD) and N-isopropyl-valproyltaurinamide (I-VTD) and evaluate their structure–pharmacokinetic–pharmacodynamic relationships with respect to anticonvulsant activity and teratogenic potential. However, their hepatotoxic potential could not be evaluated. The metabolism and pharmacokinetics of these derivatives in mice were also studied. 2. VTA lacked anticonvulsant activity, but VTD, DM-VTD and I-VTD possessed anticonvulsant activity in the Frings audiogenic seizure susceptible mice (ED(50) values of 52, 134 and 126 mg kg(−1), respectively). 3. VTA did not have any adverse effect on the reproductive outcome in the Swiss Vancouver/Fnn mice following a single i.p. injection of 600 mg kg(−1) on gestational day (GD) 8.5. VTD (600 mg kg(−1) at GD 8.5) produced an increase in embryolethality, but unlike valproic acid, it did not induce congenital malformations. DM-VTD and I-VTD (600 mg kg(−1) at GD 8.5) produced a significant increase in the incidence of gross malformations. The incidence of birth defects increased when the length of the alkyl substituent or the degree of N-alkylation increased. 4. In mice, N-alkylated VTDs underwent metabolic N-dealkylation to VTD. DM-VTD was first biotransformed to M-VTD and subsequently to VTD. I-VTD's fraction metabolized to VTD was 29%. The observed metabolic pathways suggest that active metabolites may contribute to the anticonvulsant activity of the N-alkylated VTDs and reactive intermediates may be formed during their metabolism. In mice, VTD had five to 10 times lower clearance (CL), and three times longer half-life than I-VTD and DM-VTD, making it a more attractive compound than DM-VTD and I-VTD for further development. VTD's extent of brain penetration was only half that observed for the N-alkylated taurinamides suggesting that it has a higher intrinsic activity that DM-VTD and I-VTD. 5. In conclusion, from this series of compounds, although VTD caused embryolethality, this compound emerged as the most promising new antiepileptic drug, having a preclinical spectrum characterized by the highest anticonvulsant potential, lowest potential for teratogenicity and favorable pharmacokinetics.